The hedge fund book : a training manual for professionals and capital-raising executives - Wilson, Richard C. (Wiley finance series., 2010)
An accessible guide to effectively operating in the hedge fund arenaHedge funds are now in the news more than a thousand times a day and yet it is hard to find clear, factual information about how they operate, raise capital, and invest. The Hedge Fund Book provides real-world case studies of various hedge fund managers providing a solid foundation in specialized hedge fund knowledge for both financial professionals and those aspiring to enter this field. It provides an analysis of funds within different phases of their life cycles and investment processes, and examines each cycle in ways that.